Kepemimpinan Lurah Dalam Pelaksanaan Pembangunan Di Kelurahan Rabadompu Barat Kecamatan Raba Kota Bima - Muhammad Iptidayah; Taufik Irfadat (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
Leadership is an activity to influence the behavior of other people so that they want to be directed to achieve certain goals and is a process or series of activities that are interconnected with one another, even though they do not follow a systematic sequence, the series contains activities to move, guide, direct, and supervise other people in doing something either individually or together. The method used in this research is quantitative descriptive, this method was chosen because it is based on the research object in question, the purpose of this study is to determine the role of village leadership in stimulating the community and developing the village, while the number of respondents in this study is a sample of 30 respondents and the total population is the entire community of West Rabadompu Village, Bima City, while the results of the study are surplus agricultural production as excess of the needs of farming families that are sold to meet non-primary needs. public health by empowering individuals, families and communities to foster healthy living behavior as a motivator in the village is something important where, the role or contribution of the energy and mind of a leader to provide a motivation for the community.